Preliminary phytochemical evaluation of hydroalcoholic Extract of ipomoea aquaticaforssk.from Aliyar riverine in South India - M. SASIKALA; R. SUNDARAGANAPATHY (International Journal of Pharma and Bio Sciences, 2017)
Phytoconstituents of the plants are essential source for herbal drug development. Hence, the study on detection about those is playing majorly in the pharmaceutical, botanical, agricultural and other life sciences fields. These chemicals are divided into two categories depend on its metabolism such as primary and secondary metabolites. Among this, the later one acts as ailments in treating many diseases in human and are known as traditional medicine. The aim was to distinguish the components present in the hydroalcoholic extract of the water spinach qualitatively using preliminary phytochemical tests. The experimental procedures were followed for identifying carbohydrates, proteins, aminoacids, alkaloids, glycosides, flavonoids, tannins, steroids &triterpenoids and saponins. From the analysis, primary metabolites such ascarbohydrates, proteins & aminoacids and secondary metabolites such as alkaloids, glycosides, flavonoids, tannins, steroids &triterpenoids were found positive for the tests carried out. The presence of greater number of secondary metabolites in the extract of Ipomoea aquaticaleads the detection, quantification, isolation and characterization of these constituents by means of modernized, simple & sensitive analytical techniques.